Linea de investigación: la práctica de enfermería en el contexto social - Castrillón Agudelo, María Consuelo; Benjumea, Carmen de la Cuesta; Castañeda Montoya, Mabel; Orregon Sierra, Silvia; Ceballos Velásquez, María Elena; Pérez Peláez, Liria (Investigación y Educación en Enfermería, 2013)
.